Sugammadex is changing the paradigm in neuromuscular blockade in patients with myotonic dystrophy. Issue 10 (October 2019) - Teixeira, Joana; Matias, Bernardo; Ferreira, Irene; Taleço, Tiago; Duarte, João S
Myotonic dystrophy type 1 is a rare neuromuscular disease that represents a challenge to anaesthetic management. Most of the literature does not recommend the usage of neuromuscular blocking agents, if general anaesthesia is needed in these patients. Depolarising neuromuscular blocking agents like suxamethonium are contraindicated, and there might be an increased sensitivity to non-depolarising agents like rocuronium with greater risk of postoperative residual neuromuscular blockade and consequent respiratory failure. Reversing neuromuscular blockade is also problematic as neostigmine can induce myotonic crisis, impairing normal ventilation. We discuss the use of sugammadex for neuromuscular blockade reversal, from a clinical case of a patient with myotonic dystrophy type 1 for laparoscopic cholecystectomy. The patient had a general anaesthesia with neuromuscular blockade with rocuronium. After the surgical procedure, neuromuscular blockade was safely reversed with sugammadex, guided by neuromuscular monitoring without any perioperative complications.